ANALISIS KEPUTUSAN PEMBELIAN ONLINE BERDASARKAN FAKTOR DISKON, PROGRAM PENGIRIMAN GRATIS, DAN PELAYANAN - Hermanto Joesoef (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Getting customers is not easy, especially influencing them in purchasing decisions. This problem affects all business people. Therefore, making every effort is realistic, including discount programs, free shipping, and quality service. This study aims to dig up actual information, related to purchasing behavior and its reasons. This research is studied quantitatively using multiple linear regression analysis. The respondents are the millennial generation from Jakarta who are already working, totaling 96 respondents. The results suggest that the high online buying behavior is influenced by marketing programs, especially discounts. Surprisingly, the respondents no longer differentiated between online or conventional purchases. Currently, the consideration is, of the two ways of shopping, which one is more profitable for consumers, especially at a more affordable price.